The Impact of The Characteristic of Tim Burton’s Music and Cinema on One’s Personality - Humaida, Ruby Siti (Humanities & Language: International Journal of Linguistics, Humanities, and Education, 2023)
Tim Burton, the famous film director and producer is known for his unique style that is dark, eccentric, and fantasy. His works offer a distinctive visual experience with mysterious characters and worlds. This study aims to reveal that exposure to Tim Burton's work can shape artistic sensitivity, enrich imagination, and even play an important role in a person's emotional and personality development. Case studies and content analysis of Burton's work became the research methods for this study. Repeated exposure to Burton's signature aesthetic can have a significant impact on personality development. The strange visual style and characteristics of the film's characters can stimulate a person's imagination and creativity, influencing the way they see the world and face challenges. Burton's film soundtracks are often produced by Danny Elfman, providing a deep and emotional musical backdrop, enhancing the audience's experience and expressing deep emotional nuances. Therefore, Tim Burton's visual works of art and film soundtracks are not just mere entertainment, but also elements that positively influence the development of a person's personality.